Strategi Pemasaran Semen Beku Sapi Potong di BIB Lembang - Eliza Diany; - Suryahadi; Tjahja Muhandri (Institut Pertanian Bogor, 2016)
Artificial Insemination Agency (AIA) Lembang is one of frozen semen producer in Indonesia. AIA Lembang as the first received mandate from Government of Indonesia to produce frozen semen of beef cattle and dairy cattle in order to fulfill the of Artificial Insemination (AI) in Indonesia hopefully that Indonesia doesn’t always depend on imported frozen semen. The purposes of these research are (1) to identify and analysis external and internal factors that influence marketing of frozen semen of beef cattle from AIA Lembang, (2) to compile and formulate marketing strategy of frozen semen of beef cattle regarding product, price, promotion and distribution. In this research, identifying internal and external factors that influence marketing of frozen semen of beef cattle were done at AIA Lembang. Based on internal factors (strengths and weakness) and owned by AIA Lembang and external factors (opportunities and threats) facing by AIA Lembang, marketing strategy of frozen semen of beef cattle were formulated by using IFE and EFE matrixs. IFE score for AIA Lembang is 2,944 and EFE score is 2,316. Total score in EFE matrix is describing and identifying that company is in stable position in responding to external situation. Total score for IFE matrix is 2,944, shows that the strength owned by AIA Lembang can over come it weakness fairly enough. Total score EFE matrix is 2,316, shows that AIA Lembang good enough in responding to opportunity and minimize threat. The combination of IFE and EFE scoring in IE matrix shows that AIA Lembang position is in quadrant V namely stability and growth cell. It means that AIA Lembang is stable condition. The good strategies for this region are market penetration and product development. Using SWOT analysis (Strengths, Weakness, Opportunities, and Threats) produce 7 alternative strategy formula. Based on calculation in QSP matrix, the most interesting strategy produced is increase socialization and supervision to farmers on maintainance, feeding and reproduction management as well as animal health management.